Acetone-butanol fermentation of marine macroalgae - Huesemann, Michael H.; Kuo, Li-Jung; Urquhart, Lindsay; Gill, Gary A.; Roesijadi, Guri (Bioresource technology, 2012)
► Brown macroalgae contain high concentrations of mannitol and laminarin. ► Clostridium acetobutylicum ferments these seaweed extract substrates to butanol. ► Seaweed fermentation exhibited triauxic growth: glucose–mannitol–laminarin. ► Butanol yields in seaweed and pure glucose fermentations were comparable. The objective of this study was to subject mannitol, either as a sole carbon source or in combination with glucose, and aqueous extracts of the kelp Saccharina spp., containing mannitol and laminarin, to acetone-butanol fermentation by Clostridium acetobutylicum (ATCC 824). Both mannitol and glucose were readily fermented. Mixed substrate fermentations with glucose and mannitol resulted in diauxic growth of C. acetobutylicum with glucose depletion preceding mannitol utilization. Fermentation of kelp extract exhibited triauxic growth, with an order of utilization of free glucose, mannitol, and bound glucose, presumably laminarin. The lag in laminarin utilization reflected the need for enzymatic hydrolysis of this polysaccharide into fermentable sugars. The butanol and total solvent yields were 0.12g/g and 0.16g/g, respectively, indicating that significant improvements are still needed to make industrial-scale acetone-butanol fermentations of seaweed economically feasible.